Penggunaan Collagen Stimulator di Bidang Estetika: Analisis - Mahendro, Della (Cermin Dunia Kedokteran, 2025)
Aging is a life cycle stages accompanied by physiological and anatomical changes as biological aging process. Various methods of prevention and management are used to reduce the appearance of facial aging, among others is minimally invasive procedure. Dermal fillers or soft tissue fillers are one of the minimally invasive procedures aimed at restoring facial volume and augmenting specifc areas. Dermal fillers are divided into two categories, non-biodegradable and biodegradable. Biodegradable fillers are known as collagen stimulators.The use of collagen stimulators such as polycaprolactone (PCL), calcium hydroxylapatite (CaHa), and poly-L-lactic acid (PLLA) is increasingly popular due to their ability to stimulate natural collagen production, resulting in long-lasting and natural-looking outcomes. Each type has unique characteristics, indications, and injection techniques, making product and method selection important for optimal patient results. Side efects such as edema, nodules, or infammatory reactions can be minimized with proper technique and administration by trained medical professionals. With advances in technology and improved understanding, collagen stimulators have become an efective solution for soft tissue rejuvenation and augmentation in aesthetic practice.